Predicting Neck Fluid Accumulation While Supine. Issue 4 (18th December 2015) - Vena, Daniel; Taati, Babak; Yadollahi, Azadeh
Abstract : When lying supine, fluid shifts rostrally from the legs and accumulates in the neck, which is a risk factor for obstructive sleep apnea. The objective of this study was to model neck fluid accumulation using one-time baseline measurements of body fluid, demographics, and anthropometrics. Using bioelectrical impedance, leg and neck fluid volumes (LFV and NFV) were measured continuously and simultaneously. Thirty non-obese adults (13 men) stood quietly for 5 minutes, and then lay supine for 90 minutes while fluid volumes were measured. Neck circumference (NC) was measured before and after the supine period. Results demonstrated that, compared to women, men experienced a greater increase in NC after lying supine. Furthermore, baseline LFV at the onset of lying supine was significantly correlated with ΔLFV (r = 0.44, p = 0.014) and ΔNC (r = 0.51, p = 0.008) after 90 minutes supine. The findings identify that sex and baseline LFV predict both the fluid leaving the legs and increase in NC during recumbency.